Torsional Behaviour and Finite Element Analysis of the Hybrid Laminated Composite Shafts: Comparison of VARTM with Vacuum Bagging Manufacturing Method - Mehmet Emin Taşdelen; Mehmet Halidun Keleştemur; Ercan Şevkat (Advances in Materials Science and Engineering)
Braided sleeve composite shafts are produced and their torsional behavior is investigated. The braided sleeves are slid over an Al tube to create very strong and rigid tubular form shafts and they are in the form of 2/2 twill biaxial fiber fabric that has been woven into a continuous sleeve. Carbon and glass fibers braided sleeves are used for the fabrication of the composite shafts. VARTM (vacuum assisted resin transfer molding) and Vacuum Bagging are the two different types of manufacturing methods used in the study. Torsional behaviors of the shafts are investigated experimentally in terms of fabrication methods and various composite materials parameters such as fiber types, layer thickness, and ply angles. Comparing the two methods in terms of the torque forces and strain angles, the shafts producing entirely carbon fiber show the highest torque capacities; however, considering the cost and performance criteria, the hybrid shaft made up of carbon and glass fibers is the optimum solution for average demanded properties. Additionally, FE (finite element) model of the shafts was created and analyzed by using ANSYS workbench environment. Results of finite element analysis are compared with the values of twisting angle and torque obtained by experimental tests.